Expression Of Xylose Reductase Enzyme From Spathaspora passalidarum In Saccharomyces cerevisiae. - Mamoori, Yaseen; Yahya, Abdul Ghani; AL-Jelawi, Majed (Iraqi Journal of Science, 2024)
Baker’s yeast (Saccharomyces cerevisiae) has been genetically engineered toferment the pentose sugar xylose present in lignocellulosic biomass. One of thereactions controlling the rate of xylose utilization is catalyzed by xylose reductase(XR).The current study describes xylose reductase from Spathasporapassalidarumwith NADH preference. According to JGI site the gene coding for this enzymecontains 954 nucleotides and it consists of 317 amino acids. The restriction sites forthe enzymes SacII and NotI located on the 5P´Ptermini for both the forward andreverse specific primers were designed using Lasergen 9.0 program. The genomicDNA was isolated and purified from S .passalidarum. Polymerase chain reaction(PCR) was used to amplify this gene. The amplified gene was cloned into pSN303plasmid resulting of the pYIM1 plasmid and then transformed into Escherichia coli.This plasmid was reisolated from E. coli, sequenced,and finally transformed into S.cerevisiae. The yeast transformants carrying pYIM1 plasmid named YJTY1. Thespecific activity of enzyme was 1.55 and 0.48 U/mg on NADH and NADPHrespectively for YJTY1. This enzyme has a natural preference for NADH whichmakes it a good candidate for combination with NADP+Pdependent xylitoldehydrogenase which may enable S. cerevisiae to utilize xylose under anaerobicconditions and convert it to ethanol.